Effects of children's microbiota on adipose and intestinal development in sex-matched mice persist into adulthood following a single fecal microbiota transplantation - Federica La Rosa; Maria Angela Guzzardi; Mercedes Pardo-Tendero; Monica Barone; Chiara Ruocco; Gabriele Conti; Daniele Panetta; Daria Riabitch; Silvia Bernardi; Assuero Giorgetti; Daniela Campani; Daniel Monleon; et al. (Molecular Metabolism)
Background: The global prevalence of obesity and type 2 diabetes, particularly among children, is rising, yet the long-term impacts of early-life fecal microbiota transplantation (FMT) on metabolic health remain poorly understood. Objectives: To investigate how early-life FMT from children to young, sex-matched mice influences metabolic outcomes and adipose tissue function in later, adult life. Methods: Germ-free mice were colonized with fecal microbiota from either lean children or children with obesity. The impacts on brown adipose tissue (BAT), white adipose tissue (WAT), glucose metabolism, and gut health were analyzed in male and female mice. Microbial communities and metabolite profiles were characterized using sequencing and metabolomics. Results: Male mice receiving FMT from obese donors exhibited marked BAT whitening and impaired amino acid and glucose metabolism. In contrast, female recipients developed hyperglycemia, accompanied by gut barrier dysfunction and WAT impairment. Distinct microbial and metabolite profiles were associated with these phenotypes: Collinsella and trimethylamine in females; and Paraprevotella, Collinsella, Lachnospiraceae NK4A136, Bacteroides, Coprobacillus, and multiple metabolites in males. These phenotypic effects persisted despite changes in host environment and diet. Conclusions: Early-life FMT induced long-lasting effects on the metabolic landscape, profoundly affecting adipose tissue function and systemic glucose homeostasis in adulthood. Donor dietary habits correlated with the fecal microbial profiles observed in recipient mice. These findings highlight the critical need for identifying and leveraging beneficial exposures during early development to combat obesity and diabetes.